Small animal spinal disorders : - Sharp, Nicholas J. H. (Elsevier Mosby, 2005)
Updated to keep pace with the cutting edge of technology, the new edition of this essential text has been reorganized and expanded. The broad scope of spinal disorders is covered, along with an abundance of color and black-and-white illustrations. Its well-organized approach begins with chapters on relevant anatomy and clinical examination, proceeding to delve into the most updated diagnosis, differential diagnosis, and pre-operative diagnostic aids, concluding with the review of each spinal disorder.